Dynamical effects of calcium‐sensitive potassium currents on voltage and calcium alternans. (24th January 2017) - Kennedy, Matthew; Bers, Donald M.; Chiamvimonvat, Nipavan; Sato, Daisuke
Abstract : Key points: A mathematical model of a small conductance Ca 2 + ‐activated potassium (SK) channel was developed and incorporated into a physiologically detailed ventricular myocyte model. Ca 2+ ‐sensitive K + currents promote negative intracellular Ca 2+ to membrane voltage (CAi 2+ → Vm ) coupling. Increase of Ca 2+ ‐sensitive K + currents can be responsible for electromechanically discordant alternans and quasiperiodic oscillations at the cellular level. At the tissue level, Turing‐type instability can occur when Ca 2+ ‐sensitive K + currents are increased. Abstract: Cardiac alternans is a precursor to life‐threatening arrhythmias. Alternans can be caused by instability of the membrane voltage ( V m ), instability of the intracellular Ca 2+ ( Ca i 2 + ) cycling, or both. V m dynamics and Ca i 2 + dynamics are coupled via Ca 2+ ‐sensitive currents. In cardiac myocytes, there are several Ca 2+ ‐sensitive potassium (K + ) currents such as the slowly activating delayed rectifier current ( I Ks ) and the small conductance Ca 2+ ‐activated potassium (SK) current ( I SK ). However, the role of these currents in the development of arrhythmias is not well understood. In this study, we investigated how these currents affect voltage and Ca 2+ alternans using a physiologically detailed computational model of the ventricular myocyte and mathematical analysis. We define the coupling between V m and Ca i 2 + cycling dynamics ( Ca i 2 + → V m coupling) as positive (negative) when a larger Ca 2+ transient at a given beat prolongs (shortens) the action potential duration (APD) of that beat. While positive coupling predominates at baseline, increasing I Ks and I SK promote negative Ca i 2 + → V m coupling at the cellular level. Specifically, when alternans is Ca 2+ ‐driven, electromechanically (APD–Ca 2+ ) concordant alternans becomes electromechanically discordant alternans as I Ks or I SK increase. These cellular level dynamics lead to different types of spatially discordant alternans in tissue. These findings help to shed light on the underlying mechanisms of cardiac alternans especially when the relative strength of these currents becomes larger under pathological conditions or drug administrations. Key points: A mathematical model of a small conductance Ca 2 + ‐activated potassium (SK) channel was developed and incorporated into a physiologically detailed ventricular myocyte model. Ca 2+ ‐sensitive K + currents promote negative intracellular Ca 2+ to membrane voltage (CAi 2+ → Vm ) coupling. Increase of Ca 2+ ‐sensitive K + currents can be responsible for electromechanically discordant alternans and quasiperiodic oscillations at the cellular level. At the tissue level, Turing‐type instability can occur when Ca 2+ ‐sensitive K + currents are increased.